Cross-cultural Understanding: A Dilemma for TEFL - E. Sadtono (TEFLIN, 2003)
Language is inseparable from culture, consequently when we teach a foreign language we should also teach its culture, it is an axiom. However, as English now belongs to the world as its lingua franca, used as a native language by several different nationalities, the nagging question is Ã¢â¬ËWhose culture do we have to learn? In a TEFL country such as Indonesia, teaching cross-cultural understanding is extremely difficult for various reasons and whether it is actually necessary to teach it considering the objectives of TEFL in Indonesia, the limited time allotment for teaching the language itself, the immense amount of materials to be covered, the lack of resources and the teachers questionable competence in handling the subject. This paper will discuss the background of CCU, the problems involved in teaching CCU and offer tentative solutions.